Gliomas in children - Filbin, Mariella G.; Sturm, Dominik (Seminars in neurology, 2018)
Gliomas are the most common primary central nervous system (CNS) neoplasms in children and adolescents and are thought to arise from their glial progenitors or stem cells. Although the exact cells of origin for most pediatric gliomas remain to be identified, our current understanding is that specific cell populations during CNS development are susceptible to particular oncogenic events during certain time windows and thus give rise to pediatric gliomas with distinct histological, molecular, and clinical features. These may be roughly segregated into low-grade gliomas (WHO grades I or II; including most mixed glial-neuronal tumors) and high-grade gliomas (WHO grades III or IV) according to their clinical course when untreated, even though this is not yet entirely clear for some of the recently emerging groups. The genetic and epigenetic characterization of pediatric gliomas across ages and histologies has facilitated the delineation of biologically relevant subgroups and have revealed potentially targetable alterations in some of them. This review outlines diagnostic features and molecular alterations in pediatric low- and high-grade gliomas and how the latter might be exploited with future targeted therapeutic strategies.
Gesehen am 15.04.2020